Time to Retire? The Effect of State Fiscal Policies on Retirement Decisions - Gurley-Calvez, Tami; Hill, Brian (American Economic Review, 2011)
Our research addresses the importance of state fiscal policies on the probability of retirement using a panel of individual tax return data. Results indicate that a one percentage point increase in the income or sales tax rate reduces the probability of retirement by about 8.7 percent. The evidence suggests that state spending might also affect retirement decisions but magnitudes are inconclusive. In general, the results suggest that the income effect dominates; that is, higher tax rates at the state-level reduce disposable income and decrease the probability of retiring. Results are similar in models examining single and married filers separately.